Renal Tissue Oxygenation in Essential Hypertension and Chronic Kidney Disease - Menno Pruijm; Lucie Hofmann; Bruno Vogt; Marie-Eve Muller; Maciej Piskunowicz; Matthias Stuber; Michel Burnier (International Journal of Hypertension)
Animal studies suggest that renal tissue hypoxia plays an important role in the development of renal damage in hypertension and renal diseases, yet human data were scarce due to the lack of noninvasive methods. Over the last decade, blood oxygenation level-dependent magnetic resonance imaging (BOLD-MRI), detecting deoxyhemoglobin in hypoxic renal tissue, has become a powerful tool to assess kidney oxygenation noninvasively in humans. This paper provides an overview of BOLD-MRI studies performed in patients suffering from essential hypertension or chronic kidney disease (CKD). In line with animal studies, acute changes in cortical and medullary oxygenation have been observed after the administration of medication (furosemide, blockers of the renin-angiotensin system) or alterations in sodium intake in these patient groups, underlining the important role of renal sodium handling in kidney oxygenation. In contrast, no BOLD-MRI studies have convincingly demonstrated that renal oxygenation is chronically reduced in essential hypertension or in CKD or chronically altered after long-term medication intake. More studies are required to clarify this discrepancy and to further unravel the role of renal oxygenation in the development and progression of essential hypertension and CKD in humans.